Analisis Kesalahan Berbahasa Indonesia dalam Berita Online Cikampek Info di Instagram dan Rekomendasinya Sebagai Materi Ajar Tingkat SMP - Bayu Sandi Pamungkas; Een Nurhasanah; Ferina Meliasanti (Journal on Education, 2023)
This study aims to describe the spelling errors contained in the online news text on Instagram Cikampek Info. These spelling errors include: capitalization errors, word usage errors and punctuation errors. The subject of this research is online news text as much as 32 data. The object of this study is to analyze aspects of language errors. This research method uses a descriptive qualitative method. The results of this study are recommended as teaching materials for junior high school. In this study, it has been described above regarding Indonesian language errors that occur in writing. The form of writing that is packaged in online news on internet or online media, namely the Instagram social media account @Ckpinfo which was published in August 2021. There are several mistakes in Indonesian in terms of spelling. These errors include: 1) the use of letters, including 5 capital letters and 14 italics errors; 2) word writing, including 7 base words, affixes (prefixes, inserts, suffixes and combinations of prefixes and suffixes) 4 errors, 4 rearrangements, 3 combined words, 4 prepositions, 4 particles 2 errors, abbreviations and acronyms of 6 errors, and numbers and numbers of 7 errors; 3) use of punctuation marks, including periods (.) for 5 errors, commas (,) for 7 errors, and hyphens (-) for 1 error. These errors were found in 32 news issues in August 2022.